(untitled) (Bulletin of criminological association of Ukraine, 2024)
The process of documenting war crimes is one of the priority areas of interaction between investigators and other bodies and units, because documenting is a way of preserving evidence of war crimes that may be hidden or destroyed over time. In the conditions of active hostilities, documenting such offenses is impossible without the involvement of representatives of the Armed Forces of Ukraine, because, as a rule, it is they who possess a significant amount of information about factual data that can be recognized as evidence in criminal proceedings. After all, it is the military personnel who carry out various military operations in the occupied territories who are the first to arrive in the liberated areas, and the pre-trial investigation bodies cannot arrive immediately or do not have objective access to the place where war crimes were committed. In order to timely and properly notify law enforcement agencies about the commission of war crimes, complete collection, preservation and transfer of potential evidence to pre-trial investigation bodies, based on the analysis of court practice, provisions of criminal procedural legislation, practical advisors and recommendations, the author of the article developed proposals regarding the procedure for involving representatives of the Armed Forces of Ukraine at the beginning of the pre-trial investigation of war crimes, their transfer of items and documents discovered on the battlefield or de-occupied territories, which can be recognized as physical evidence and have evidentiary value in criminal proceedings regarding war crimes